(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The food supplements industry, as well as, the wellness trend is undergoing a tremendous growth. In case you are seeking to sell in such space or make policy likewise direction, it is relevant to possess a feel of what actually sparks the buys. In practice, it is crucial. We were not keen on being confined to such general beliefs and ways that we could have known what is a major role, the demographic factors like age and gender, the facility of the real purchase of the product and effect of the own state of health. A survey that was well structured gathered information on 143 individuals and the information was analyzed using SPSS. The analytical methods were ANOVA, reliability test, descriptive statistics, independent samples t-tests and multivariate regression analysis. This is more or less the complete tract of such buying behavior study of analysis. A single dominant pattern emerged which was that the first age was not a simple variable, but the most predictive of whether an individual would intend to buy supplements. The gender was also originating to be important and this confirms that marketing is not about a one size fits all strategy. This is a fine point but pre-existing medical conditions had it that the former would be more reliant on the advice of a doctor in making the purchase as expected. Notably, they did not demonstrate a greater purchase intention much higher than no conditions. This means that the presence of a condition renders the buying process to be more cautious and advice based process as opposed to being an eagerness based process. The majority of the cases depended on the fact that a single largest predictor was accessibility. Non price, but just first, non-brand. How convenient will it be to me to find and get this product? This fact leads to logistics and distribution.